Effect of Price, Location, and Service Quality on Consumer Satisfaction - Djakaria, Hanifah; Yani, David Ahmad; Mardiana, Mardiana; Wibowo, Teguh Setiawan; Iswadi, Udi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research will aim to analyze the influence of price, location and service quality on consumer satisfaction at the Micro Cell counter. This research uses quantitative methods. The data in this research was collected through a survey method using purposive sampling techniques. Questionnaires were distributed to 96 respondents who had made a purchase at the Micro Cell counter at least once. The data resulting from distributing the questionnaire will be processed using the SPSS software analysis tool. The selected results and analysis tests include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing via t test, F test, and analysis of the coefficient of determination (R2). From the research results and data analysis results, the following conclusion can be drawn: there is a positive but not significant influence of the price variable on consumer satisfaction at Micro Cell counters. There is a positive and significant influence of location variables on consumer satisfaction at Micro Cell counters. There is a positive and significant influence of the service quality variable on Micro Cell counter consumer satisfaction. The results of this research show that Micro Cell counters need to maintain optimal service quality so that consumer satisfaction is met, thereby increasing sales at Micro Cell counters.